Religious Schools and Their Role in Establishing the Correct Doctrine - A Fundamental Doctrinal Study in the Reality of Kirkuk City - Qasim Adnan Saleh, (Islamic Sciences Journal, 2025)
This study explores the role of religious schools in Kirkuk in consolidating sound Islamic creed according to the methodology of Ahl al-Sunnah wa’l-Jamaʿah, particularly the Ashʿari and Maturidi schools, through a foundational analysis combining historical background and contemporary reality. The theoretical part defines the correct creed and its principles, highlighting the role of religious schools in preserving this theological heritage, and explaining the Ashʿari and Maturidi approach in harmonizing reason and revelation while affirming Allah’s transcendence. It, then, examines the historical development of religious schools in Kirkuk, their role in teaching key creedal texts such as *al-ʿAqaʾid al-Nasafiyyah* and *al-Jawharah fi al-Tawhid*, and their impact in producing scholars and preachers who upheld a balanced theological discourse. The research emphasizes these schools’ contribution to maintaining Sunni identity, reducing theological disputes, and fostering intellectual and religious stability. It also analyzes the intellectual and administrative challenges they face, such as weak public theological awareness, decline in structured teaching, shortage of qualified staff, and lack of institutional coordination. Proposed measures include curriculum modernization, teacher training, media engagement, and establishing a unified coordinating body. The study concludes that religious schools in Kirkuk are a cornerstone in safeguarding doctrinal identity, and that revitalizing their role is essential to preserve the moderation of religious discourse and align it with contemporary needs.